A GLIMPSE OF TOLERANCE IN THE CONCEPT OF ISLAM (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article analyzes the principles of tolerance in Islam based on history, divine sources, and the views of Western thinkers. Virtues such as patience, forgiveness, and justice occupy a special place in the Quran and Sunnah. Western historians are moving away from the view that Islam was spread by the sword and are recognizing its humane and peace-loving characteristics.